Pengaruh Kemampuan Pengideran Pasar dan Inovasi Produk terhadap Kinerja Pemasaran serta Keunggulan Kompetitif pada UMKM Bordir di Kabupaten Pasuruan - Nova Verawati; Nuraeni Nuraeni; Any Urwatul Wusko (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in the embroidery sector face increasing competitive challenges, requiring the ability to recognize market changes and develop product innovations to improve marketing performance and gain competitive advantage. This study aims to evaluate the influence of Market Sensing Capabilities and Product Innovation on Marketing Performance and Competitive Advantage of embroidery MSMEs in Pasuruan Regency. The research employed a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM), analyzed with SmartPLS 4. The sample consisted of 67 active MSME actors selected using a census technique. The analysis results indicate that Market Sensing Capabilities have a significant effect on Marketing Performance but not on Competitive Advantage. Similarly, Product Innovation significantly affects Marketing Performance, yet shows no significant direct influence on Competitive Advantage. Another key finding reveals that Marketing Performance has a significant impact on Competitive Advantage, suggesting that enhancing competitive strength is more effectively achieved through improved marketing performance. Therefore, the development of market capabilities and product innovation strategies should be prioritized to strengthen marketing outcomes as a foundation for sustainable competitive advantage.